Does Learning Through Movement Improve Academic Performance in Primary Schoolchildren? A Systematic Review - Petrigna, Luca; Thomas, Ewan; Brusa, Jessica; Rizzo, Federica; Scardina, Antonino; Galassi, Claudia; Lo Verde, Daniela; Caramazza, Giovanni; Bellafiore, Marianna (Frontiers in Pediatrics, 2022)
Physically active children have greater motor competence and a faster maturation compared to their sedentary peers. Recent research also suggests that physical activity during childhood may also promote cognitive development and therefore improve academic performance. The aim of this study is to understand if physically active academic lessons may improve academic achievement in primary schoolchildren. A systematic review following the PRISMA guidelines was conducted. The search was performed on the following database: PubMed, Web of Science, Scopus, Education Resources Information Center(ERIC), and PsycInfo(APA). Studies evaluating schoolchildren aged between 3-11 years old, taking part to educational contexts which include physical activity and natural environments evaluating physical fitness and / or educational outcomes were included. A total of 54 studies (for a total sample of 29460 schoolchildren) were considered eligible and included in the qualitative synthesis. The Effective Public Health Practice Project risk of bias assessment revealed a moderate quality of the included studies with only two considered week. Despite differences in the retrieved protocols, physically active academic lessons improve the total time engaged in physical activity, motor skills and/or academic performance. The results of this review suggest that learning through movement is an effective, low cost and enjoyable strategy for elementary schoolchildren.